Proceedings of the 41st Annual Hawaii International Conference on System Sciences (HICSS 2008) 2008
DOI: 10.1109/hicss.2008.119
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of IT Outsourcing Relationships: A Conceptual Model

Abstract: How can relationship quality in outsourcing partnerships be achieved, sustained, and improved? In this paper we present a conceptual model that focuses on the identification of the relevant determinants for a successful IT outsourcing relationship as well as on the operationalization IT outsourcing relationship quality. We contribute to existing relationship literature by thoroughly examining existing constructs and, if applicable, spliting and redistributing them. We also consider additional relationship qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…To enhance the relationship it is important to understand the exchange partners. The shared domain knowledge and a common "language" between the parties are important facets of alignment and thus relationship quality (Blumenberg et al 2008).…”
Section: Relationship Quality and Its Determinantsmentioning
confidence: 99%
“…To enhance the relationship it is important to understand the exchange partners. The shared domain knowledge and a common "language" between the parties are important facets of alignment and thus relationship quality (Blumenberg et al 2008).…”
Section: Relationship Quality and Its Determinantsmentioning
confidence: 99%
“…Many researchers [4,[13][14][15][16][17][18] have investigated that knowledge sharing, trust and commitment as key determinants of outsourcing success. In addition, many studies has emphasized the significance of software requirements knowledge transfer to ensure the software quality and customer satisfaction [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Handley and Benton Jr [39] have found that, completeness of contract is important in determining the performance of IT offshoring. Furthermore, the model proposed by Blumenberg, Beimborn [40]shows that, completeness of contract affects the success of the relationship between partners. [43] has showed that, the internal technical capability for the organization is an important issue related to IT offshoring.…”
Section: It Offshoring Success Factorsmentioning
confidence: 99%